Responses of civil society organisations to HIV and AIDS in Nelson Mandela Bay metro - Mabaso, Bongani Alson (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil (Industrial Psychology. HIV/AIDS Management))--Stellenbosch University, 2008.